Arab political movements in Israel: different ideologies and disparate rhetoric - Khatib, Mouad (University of Cape Town, 2020)
Arab Palestinians in Israel live under highly complex circumstances. In 1948, when they became Israeli citizens, they found themselves facing challenges at different levels: national, social, political, financial, educational, as well as the very challenge of existence. The Palestinian community in Israel underwent various stages of development and witnessed major events under the new Israeli rule, bringing about fundamental changes in their lives, their attitudes, and consequently, their rhetoric. Arab politicians, particularly those who represent Arab Palestinians in the Knesset (the Israeli Parliament), often find themselves compelled to adjust the approach and rhetoric they use to address the Arab public. They do it not only to satisfy the Arab public's expectations, but also to adapt to the ever-changing Israeli political atmosphere and to avoid conflict with the Jewish public, the majority of whom, as polls indicate, are not happy about Arab representation in the Israeli Knesset. Discussion of the rhetoric used by the Arab parties in Israel that represent the Palestinian people who before 1948 were a majority and after that year became a minority that suffers inequality, oppression, and discrimination, is important in order to understand how argumentation and methods of persuasion are influenced by the kind of circumstances that national minorities like Palestinians in Israel experience. This thesis will examine the rhetoric used by the main Arab political movements in Israel when addressing several key issues that are currently the subject of heated debate and are expected to have remarkable effects on Arabs and their lives as non-Jews in the Israeli state. These issues are: Arab representation in the Israeli Parliament, recognition of Israel as a "Jewish State", and National Service for Arabs. The largest part of the research will focus on the Arab representation in the Knesset, being the most controversial topic among the Arab minority in Israel, and which also determines to a great extent the positions of the parties on other issues. After reviewing the position of each party/political movement on each of these topics, I intend to analyze the rhetoric each of them uses to defend their position or promote it to gain the support of the public, especially during parliamentary elections. Is the rhetoric of Arab parties in Israel coherent and harmonious as it represents a Palestinian minority dealing with Israeli policies as a collective entity, or does each of the parties have a unique rhetoric of its own, based on its ideology and agendas? What are the arguments that these parties use to justify their views, and how do they present these arguments? Are the arguments used by each party from the deliberative branch of rhetoric, the forensic, or the epideictic? Do Arab politicians mostly use ethos, pathos, or logos to persuade the audience and gain their support? This thesis will answer these questions by analyzing the parties' publications and official statements and political charters, and it will show that the positions, the rhetoric, and the argumentation of the different Arab parties are far from being homogeneous, and are highly influenced by their ideological background.